2023
DOI: 10.2337/db23-114-lb
|View full text |Cite
|
Sign up to set email alerts
|

114-LB: Early Time-Restricted Feeding Reduces Time in Elevated Glucose Range in Adults With Prediabetes

Abstract: Objective: Early time-restricted feeding (eTRF) is an intermittent fasting strategy restricting caloric intake to the first 6-8 hours of the day. While previous studies have shown that eTRF improves glycemia, it is unclear if the effect is due to associated weight loss or metabolic benefits of the feeding strategy itself. In this study, we evaluated the weight-independent effects of eTRF on glycemia using multiple CGM-based time in range (TIR) metrics. Methods: We conducted a randomized 7-day is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Early time-restricted feeding (eTRF) is an intermittent fasting strategy restricting caloric intake to the first 6–8 h of the day. Furthermore, previous studies in humans have shown that eTRF improves glucose control in adults with prediabetes and high BMI [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early time-restricted feeding (eTRF) is an intermittent fasting strategy restricting caloric intake to the first 6–8 h of the day. Furthermore, previous studies in humans have shown that eTRF improves glucose control in adults with prediabetes and high BMI [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…While most randomized clinical trials studying IF interventions in humans have shown a reduction in T2DM risk parameters, such as fasting glucose and insulin levels, it is important to acknowledge that there are exceptions to this trend. Some studies may not observe significant improvements in these biomarkers following intermittent fasting interventions [ 18 , 30 ]. The reasons for these exceptions could be multifactorial and may include variations in study design, differences in participant characteristics [ 34 ], effects of fasting on reproductive hormone levels in humans, especially for menopausal women [ 35 ], or variations in the duration or intensity of the intermittent fasting protocols employed.…”
Section: Introductionmentioning
confidence: 99%